2020
DOI: 10.47197/retos.v1i40.81775
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre variables antropométricas y calidad de movimientos fundamentales en una muestra de escolares chilenos entre 12 y 14 años (Association between anthropometric variables and quality of fundamental movements in a sample of Chilean schoolchil

Abstract: Introducción: A pesar de que existe una relación entre el sobrepeso, actividad física y calidad de movimiento, no está clara la relación entre otras variables relacionadas con la composición corporal y la calidad de patrones de movimiento fundamentales, por lo que el objetivo de este estudio fue determinar la relación entre variables antropométricas y calidad de movimientos fundamentales en escolares. Material y Método: Estudio observacional analítico transversal. Se evaluaron 18 estudiantes (11 hombres) de 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Although there is limited research on RPI in the context of fitness assessments, it is speculated that an optimal RPI score may vary depending on the test (e.g., jump and strength assessment); therefore, the RPI should be used with caution ( Silva et al, 2016 ). Other indexes, such as the WHR, could be feasible ( Ross et al, 2000 ) as this measure has shown a relationship with some fitness markers (e.g., deep squat, in-line lunge) ( Lavados et al, 2020 ). Nevertheless, the relationship between these indices and fitness tests seems to be influenced by several factors, as it has shown a nonlinear distribution in all studies ( Lopes et al, 2017 ; Cossio-Bolaños et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited research on RPI in the context of fitness assessments, it is speculated that an optimal RPI score may vary depending on the test (e.g., jump and strength assessment); therefore, the RPI should be used with caution ( Silva et al, 2016 ). Other indexes, such as the WHR, could be feasible ( Ross et al, 2000 ) as this measure has shown a relationship with some fitness markers (e.g., deep squat, in-line lunge) ( Lavados et al, 2020 ). Nevertheless, the relationship between these indices and fitness tests seems to be influenced by several factors, as it has shown a nonlinear distribution in all studies ( Lopes et al, 2017 ; Cossio-Bolaños et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%